Pertanggungjawaban Aparat atas Kesalahan Prosedural dalam Kasus Salah Tangkap Ditinjau dari Filsafat Hukum - Hidayat, Muhammad Rahmadzani (Media Hukum Indonesia (MHI), 2025)
Procedural errors by law enforcement officers that result in wrongful arrests constitute a serious violation of human rights and fundamental principles of justice. This study examines the mechanisms of legal accountability for officers responsible for such errors and analyzes them through the lens of legal philosophy. Using a normative juridical method, this research identifies criminal, civil, administrative, and pretrial remedies as instruments to correct unlawful arrests. Philosophically, the perspectives of Aristotle, Fuller, and Radbruch show that wrongful arrest is not merely a technical mistake but a moral failure that undermines the state's legitimacy in exercising its authority. Therefore, holding officers accountable is essential not only for legal certainty but also for safeguarding substantive justice and restoring public trust in the criminal justice system.